2023
DOI: 10.1101/2023.02.09.527910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A highly efficient human cell-free translation system

Abstract: Cell-free protein synthesis (CFPS) systems enable easyin vitroexpression of proteins with many scientific, industrial, and therapeutic applications. Here we present an optimized, highly efficient human cell-free translation system that bypasses many limitations of currently usedin vitrosystems. This CFPS system is based on extracts from human HEK293T cells engineered to endogenously express GADD34 and K3L proteins, which suppress phosphorylation of translation initiation factor eIF2α. Overexpression of GADD34 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…In the present study, we demonstrated that cell-free protein synthesis based on CHO cell lysates can be more efficient and cost-effective by modifying the host cells. The potential of enhancing cell-free cap-dependent translation initiation was recently demonstrated by overexpression of GADD34 and K3L in human cells [ 48 ]. It was shown that increased levels of the truncated protein phosphatase GADD34 and the vaccinia virus protein K3L prior to cell disruption resulted in decreased eIF2α phosphorylation and increased cell-free protein production based on human cell lysate.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that cell-free protein synthesis based on CHO cell lysates can be more efficient and cost-effective by modifying the host cells. The potential of enhancing cell-free cap-dependent translation initiation was recently demonstrated by overexpression of GADD34 and K3L in human cells [ 48 ]. It was shown that increased levels of the truncated protein phosphatase GADD34 and the vaccinia virus protein K3L prior to cell disruption resulted in decreased eIF2α phosphorylation and increased cell-free protein production based on human cell lysate.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro translation reactions were performed using HEK293T pSB-HygB-GADD34-K3L translation-competent cell extract, as previously described (Aleksashin et al 2023). Translation reactions contained 50% translation-competent cell extract, 52 mM HEPES pH 7.4 (Takara), 35 mM potassium glutamate (Sigma), 1.75 mM Mg(OAc)2 (Invitrogen), 0.55 mM spermidine (Sigma), 1.5% Glycerol (Fisher Scientific), 0.7 mM putrescine (Sigma), 5 mM DTT (Thermo Scientific), 1.25 mM ATP (Thermo Fisher Scientific), 0.12 mM GTP (Thermo Fisher Scientific), 10 mM L-Arg; 6.7 mM each of L-Gln, L-Ile, L-Leu, L-Lys, L-Thr, L-Val; 3.3 mM each of L-Ala, L-Asp, L-Asn, L-Glu, Gly, L-His, L-Phe, L-Pro, L-Ser, L-Tyr; 1.7 mM each of L-Cys, L-Met; 0.8 mM L-Trp, 20 mM creatine phosphate (Roche), 60 µg/mL creatine kinase (Roche), 4.65 µg/mL myokinase (Sigma), 0.48 µg/mL nucleoside-diphosphate kinase (Sigma), 0.3 U/mL inorganic pyrophosphatase (Thermo Fisher Scientific), 100 µg/mL total calf tRNA (Sigma), 0.8 U/μL RiboLock RNase inhibitor (Thermo Scientific), and 1000 ng of the corresponding mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293T pSB-HygB-GADD34-K3L cells (Aleksashin et al 2023) were maintained in DMEM media (Gibco) supplemented with 10% Tet-system approved FBS (Gibco) and 1% Pen/Strep (Gibco). Cells were grown at 37 °C in 5% carbon dioxide and 100% humidity.…”
Section: Hek293t Psb-hygb-gadd34-k3l Cells and Extract Preparationmentioning
confidence: 99%
See 2 more Smart Citations